Hyposmia and Dysgeusia in COVID-19: Indication to Swab Test and Clue of CNS Involvement - Bax, Francesco (Neurol Clin Pract, 2021)
OBJECTIVE: To evaluate the prevalence of hyposmia and dysgeusia in patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and their temporal relationship with the onset of other symptoms. METHODS: We performed a retrospective analysis of patients admitted during the month of March 2020 to the nonintensive COVID unit of Udine University Hospital on the basis of a positive swab test and/or of clinical-radiologic signs of SARS-CoV-2 infection. Patients were interviewed with a standardized questionnaire. Clinical and laboratory data were collected. Data were analyzed with descriptive statistics, and results expressed as point estimates and 95% confidence intervals (CIs). RESULTS: Of 141 patients admitted, 93 were interviewed. Hyposmia and dysgeusia were present in 58 cases (62.4%). In 22.4% of them, olfactory and gustatory impairment clearly preceded systemic symptoms. The presence of active smoking was very limited in both groups: 8.6% in hyposmic vs 2.9% in normosmic patients (odds ratio 3.2; 95% CI 0.3–28.6). Moreover, total leukocytes and neutrophils count were respectively 23% (effect estimate 1.23; 95% CI 1.06–1.42) and 29% (effect estimate 1.29; 95% CI 1.07–1.54) lower in the hyposmic cohort. No difference was found for other inflammatory biomarkers. CONCLUSIONS: Hyposmia and dysgeusia are common in SARS-CoV-2 infection and can precede systemic symptoms. They should be actively searched and prompt close monitoring and isolation until infection is confirmed or disproven. The lower number of total leukocytes and neutrophils in hyposmic patients might indicate an early-phase virus-induced cytopenia.